Pembelajaran Hafalan Al Quran di Sekolah Heterogen - Rohmah, Liatul Rohmah; Zuhriyah, Lailatuzz (JOM, 2024)
Competition in the world of education makes schools compete to improve the quality of their students by creating additional curricula. Private Integrated Islamic Primary School (SDIT) and Madrasah succeed in attracting customers with their typical curriculum, one of which is learning the recitation of the Quran. As an elementary school, SDN (Sekolah Dasar Negeri/Public Elementary School) Kampungdalem 1 Tulungagung added its curriculum with the learning of recitation of the Quran. The research question is: what is the learning method of recitation of the Quran in SDN 1 Kampungdalem Tulungagung?, How is the implementation of the learning method of recitation of the Quran in SDN 1 Kampungdalem Tulungagung? How and implications of learning the recitation of the Quran in SDN 1 Kampungdalem Tulungagang. The research methods used are qualitative research methods and data collection techniques through observation, interviews, and documentation with data analysis of interactive analysis. The results of this study are: the method used in the special class is wahdah, jama', sima'i, takrir, and muraja'ah with the implementation of reading verses per verse and followed together 3 to 5 times, sima'i and takrir of the Quran recording at home as much as 10-20x, muraja'ah as often as possible. In the regular class, the methods used include wahdah, tallaqi, simai, takri, and muraja'ah. The implementation is reading verses per verse and followed by students individually, listening to the recording of the Quran repeatedly 10-20x by listening to their Indonesian writing at home, muraja'ah repeatedly. The implication is that students can memorize up to 3 juz even though they have not been able to read and write the Quran with the method used, and students are more vigorous, learning spirit, discipline, and related to the program of recitation of the Quran at school.